Dukungan Sosial Dan Penerimaan Diri Anak Binaan - amalia, gina (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Islam Raden Rahmat Malang, 2023)
Fostered children who undergo the formation period experience several changes in their lives where they will live separately from their parents, family, friends, society, loss of freedom to live life like teenagers in general, increasingly limited rights, and the title of prisoner attached to them. The purpose of this study was to determine the effect of social support on self-acceptance in fostered children in LPKA Class I Martapura. This research method uses a quantitative approach with simple linear regression analysis. Sampling in this study used non-probability sampling techniques with saturated sample methods. The subjects of this study were 45 subjects at LPKA Class I Martapura. The scale used in this study is the scale of social support and self-acceptance, with the scaling model being the Likert scale. The result of this study is that there is a significant influence between social support and self-acceptance.